PENGARUH KONFLIK PEKERJAAN DAN STRESS KERJA TERHADAP KINERJA KARYAWAN (Studi Pada Karyawan PT. Royal Impala Divisi Regulator Kota Tangerang) - Dian Apriliani; Ratu Erlina Gentari (Sains Manajemen, 2016)
The study to determine the work conflict and job stress on employee performance PT. Royal Impala, the independent variables in study is Work Conflict and Job Stress and thedependent variable is employee of performance.The research model used in this study uses quantitative methods to study associative explanasi level is to determine the impactbetween variables, the data sources of data are primary data and secondary data in the from of questionaires. The statistical method use is test of normality, test of linearity, themulticolinearity test, heteroscedasticity test, autocorrelation analysis, multiple regression analysis, partial correlation analysis, determination analysis. Based of the calculation,calculate the velue of is equal to 54,858 while the table is 3,49 (54,858 > 3,49) means to Ho is rejected and Ha accepted meaning there is be positive and significant affect betweenwork conflict and job stress on employee of performance PT. Royal Impala Tangerang City.